Debt securisation and debt trading under the Islamic law : a case study of Cagamas Bhd - Mahadi Ahmad (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2009)
It is a well known fact that one of the duties of the financial institutions is to finance some viable capital intensive projects on deferred payment basis that last for a lengthy period of time, often ranges between 15 to 30 years. This process, therefore, usually leads to accumulation of sizable financial claims owed to the banks by the financees. As a result of this, the bank may resort to sell those illiquid assets which are the financial claims on cash basis in order to have more liquidity to further finance other prospective financees. To achieve this purpose, the Malaysian government in 1986 established Cagamas Bhd to act as a catalyst for house ownership in the country, by purchasing those receivables. This type of transaction generates a lot of controversies among the contemporary experts in the field of Islamic finance. Therefore, the purpose of this research is to examine the seemingly unending problems which often arise through the process and the period involved, as well as the controversies generated by this type of transaction among the Muslim Jurists. Also, this is to proffer some vibrant solutions which may justify the aim of the government on the issue and which would be accommodated within the parameters of maqasid al-Shari'ah. The methodology adopted in this research is a qualitative one. During the course of this research, it is discovered that the arguments of the earlier Muslim jurists on inability of the seller to deliver the debt could be narrowed down if the debt is in form of a commodity through the government regulations on the supervision of normal sale of debt. Similarly, a monetized debt, subject to the rules of sarf, is however found capable of being alternated by a transaction that will allow Cagamas Bhd to own a stake on the project that generates the debts through the issuance of tradable sukuk backed by that project and pay the bank from the proceeds of the sukuk.